Catering to the needs of their adult learners: The role of the faculty / Fatin Zawani Zainal Azaim - Zainal Azaim, Fatin Zawani (2011)
This study investigates the perceptions of postgraduate students, the challenges of adult learners as they seek a master's degree and the role of the faculty in catering to the needs of their adult learners. This study adapted the conceptual framework of Cross (1981), Hillage and Aston (2001) and Mackeracher, Stuart and Potter (2006), three main challenges were discussed; physical and material / situational, attitudinal and structural. The same categories were applied to determine the role of the faculty in catering to the needs of their adult learners. Four categories were develop to identify the Masters in Education students' perceptions of their experiences as a student in the faculty; perceptions of the course, class, assignments and lecturers. A questionnaire was utilized to uncover the postgraduate students' perceptions, challenges of adult learners, and the role of the faculty. Findings depict positive perceptions from the respondents on the course and class provided to them but the respondents were having problems on the number of assignments given and the time allocated to complete the assignments.It is also reported that the lecturers were difficult to contact for discussion. All three categories of challenges were found however attitudinal challenges were not the major concern. The challenges are multiple-conflicting responsibilities, job commitments, time constraints, lack of guidance and counseling services, some courses offered do not appeal to the students' interest and inadequate services from the library. In terms of the faculty role, the respondents reported that the faculty lack in several areas such as; funding support, guidance and counseling supports, lack of updated reading materials from the library, limited choices of courses and the flexibility to choose their own elective courses. The implications of the study include the importance of managing and balancing responsibilities, time management, acknowledging the importance of the various responsibilities, tolerance and support from family, educators and the faculty. The education providers and course designers are advised to consider the various roles played by adult learners before developing course outline and schemes of work.